Indoor air quality assessment to design a model for indoor air quality management and health impact assessment in Northern Thailand - Thongsumrit Jitvisut; Chantara Somporn; Naksen Warangkana; Bootdee Susira; Payam Mallika; Wiriya Wan (E3S Web of Conferences, 2023)
Indoor air quality (IAQ) has become an important area of concern these days and tends to be more serious to human health as well as resident convenience, especially in smoke haze season (February - April) in Upper Northern Thailand (UNT). Indoor air monitoring and model development for controlling the air quality indoors is necessary for all buildings, particularly in urban areas and polluted areas. This study aims i) to study indoor air quality, ii) to assess health impacts and factors related to indoor air quality, and iii) to develop an effective model for controlling indoor air quality in Sub-district Health Promoting Hospital (HP) and Early Childhood Development Center (ED). Temperature, relative humidity, air movement, PM2.5, PM10, Carbon Dioxide (CO2), Carbon Monoxide (CO), Ozone (O3), Formaldehyde (CH2O), Total Volatile Organic Compound (TVOC), Total bacterial and fungal were used to evaluate indoor air quality. It was found that PM2.5 and PM10 concentrations in all buildings exceeded indoor air quality standards. Moreover, CO2 concentration was higher than recommended levels, especially during the daytime. HP and ED found high values of total bacteria and total fungi, which were higher than recommended level. The indoor air quality management model of a clean room that involved with the calculation of total airflow in cubic feet per hour was created and a specific size of air cleaner for the room was selected. The results showed that PM2.5 and PM10 concentrations including other parameters of the selected rooms were reduced to the recommended levels after implementing the rooms. This result indicated the effectiveness of developing an indoor air quality management model. Thus, this model can be used as a successful study case for other HP and ED, leading to a positive impact on building occupant health.